Multilayer conductive foam

By using nano silver wires and high-performance materials such as graphene or boron nitride in conductive foam materials, combined with quantum doped polymer materials, bio-based nanocomposite materials and antioxidants, an efficient electromagnetic shielding and thermal conductivity network is constructed, which solves the shortcomings of conductive foam materials in electromagnetic shielding and thermal conductivity, and achieves high-performance and high-stability material effects.

CN119730219APending Publication Date: 2025-03-28SHENZHEN HFC SHIELDING PRODS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411923857.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing conductive foam materials have shortcomings in electromagnetic shielding and thermal conductivity and heat dissipation, and cannot meet the needs of modern electronic equipment for high performance and high stability.

Method used

Nanosilver wire is used as the conductive material, combined with graphene or boron nitride as the thermal conductivity material, and an efficient electromagnetic shielding and thermal conductivity network is constructed through lamination or bonding processes, and quantum doped polymer materials, bio-based nanocomposite materials and antioxidants are added to the composite intermediate layer.

Benefits of technology

It achieves excellent electromagnetic shielding effect and fast heat conduction, avoids the occurrence of local overheating, and improves the stability and service life of the material. It is suitable for electronic equipment with high requirements for electromagnetic shielding and heat dissipation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730219A_ABST
    Figure CN119730219A_ABST
Patent Text Reader

Abstract

The invention discloses a multilayer conductive foam, and relates to the technical field of conductive foams, and the multilayer conductive foam comprises the following components: a conductive material, a heat conduction material, a quantum dot doped polymer material, a bio-based nano composite material and a composite intermediate layer which are compositely assembled with other foam layers through a lamination or bonding process, and a reserved cavity; according to the invention, the silver nanowire is adopted as a conductive material, and graphene or boron nitride is combined as a heat conduction material, so that an efficient electromagnetic shielding and heat conduction network is constructed, and the silver nanowire can effectively block penetration of electromagnetic waves and provide an excellent electromagnetic shielding effect due to excellent conductivity; graphene and boron nitride are used as high-performance heat conduction materials, heat can be rapidly conducted out, the phenomenon of local overheating is avoided, the two materials are combined for use, the multilayer conductive foam is excellent in electromagnetic shielding and heat conduction performance, and the multilayer conductive foam is suitable for electronic equipment with high electromagnetic shielding and heat dissipation requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of conductive foam, in particular to a multi-layer conductive foam. Background Art

[0002] With the rapid development of electronic technology, various electronic devices are being used more and more widely, and the requirements for electromagnetic shielding and thermal conductivity are becoming higher and higher. Traditional conductive foam materials have certain limitations in electromagnetic shielding and thermal conductivity, and cannot meet the needs of modern electronic equipment for high-performance materials.

[0003] In traditional technology, on the one hand, the electromagnetic shielding effect is crucial to the normal operation of electronic equipment. In a high-frequency electromagnetic environment, if the material cannot effectively block the penetration of electromagnetic waves, it may cause signal interference between electronic components inside the device, and even cause equipment failure. Although traditional conductive foam materials have certain conductive properties, their electromagnetic shielding effect still needs to be improved. On the other hand, with the increasing integration of electronic equipment, the heat dissipation problem is becoming increasingly prominent. If the material cannot quickly conduct the heat generated inside the device, it may cause the device to overheat and affect the stability and service life of the device.

[0004] In summary, the existing conductive foam materials have deficiencies in electromagnetic shielding and thermal conductivity and heat dissipation, and cannot meet the requirements of modern electronic equipment for high performance and high stability. Therefore, it is particularly important to develop a multi-layer conductive foam. Summary of the invention

[0005] The purpose of the present invention is to make up for the shortcomings of the prior art and provide a multi-layer conductive foam, which can construct a high-efficiency electromagnetic shielding and thermal conduction network by using nano silver wire as a conductive material and combining graphene or boron nitride as a thermal conductive material. Nano silver wire can effectively block the penetration of electromagnetic waves due to its excellent conductive properties and provide excellent electromagnetic shielding effect. At the same time, graphene and boron nitride, as high-performance thermal conductive materials, can quickly conduct heat away to avoid the occurrence of local overheating.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: a multi-layer conductive foam, the formula of which includes the following components: conductive material, thermal conductive material, quantum dot-doped polymer material and bio-based nanocomposite material and a composite middle layer compositely assembled with other foam layers through lamination or bonding process and reserved cavity;

[0007] The conductive material is nano silver wire;

[0008] The thermal conductive material is graphene or boron nitride;

[0009] The quantum dots doped with the polymer material are cadmium sulfide quantum dots, and the polymer is a polyurethane polymer;

[0010] The bio-based nanocomposite material is a composite of chitin nanofibers and silver nanoparticles;

[0011] The composite middle layer is compositely assembled with other foam layers through lamination or bonding process;

[0012] The reserved cavity is filled with sound absorbing material or other functional substances by injection filling or vacuum filling process.

[0013] Furthermore, the conductive material is nano silver wire, the diameter of which is in the range of 10nm-100nm, the length of which is in the range of 1μm-100μm, and the mass fraction of which in the composite intermediate layer is 5%-20%.

[0014] Furthermore, the thermal conductive material is graphene or boron nitride, wherein the number of graphene layers is 1-10, the sheet diameter range is 1μm-100μm, and the mass fraction in the composite middle layer is 3%-15%, and the boron nitride is hexagonal boron nitride, and its particle size range is 0.5μm-50μm, and the mass fraction in the composite middle layer is 3%-15%.

[0015] Furthermore, the quantum dots in the quantum dot-doped polymer material are cadmium sulfide quantum dots, the particle size range of which is 2nm-20nm, the mass fraction of which in the quantum dot-doped polymer material is 1%-10%, and the polymer is a polyurethane polymer.

[0016] Furthermore, the bio-based nanocomposite material is a composite of chitin nanofibers and silver nanoparticles, the chitin nanofibers have a diameter range of 10nm-100nm, a length range of 1μm-100μm, the silver nanoparticles have a particle size range of 5nm-50nm, and the mass fraction of the silver nanoparticles in the bio-based nanocomposite material is 5%-30%.

[0017] Furthermore, the composite middle layer is compositely assembled with other foam layers by lamination or bonding process, the lamination pressure range is 0.5MPa-5MPa, the adhesive is epoxy resin adhesive, and the coating amount of the adhesive on the bonding interface is 10g / m 2 -100g / m 2 .

[0018] Furthermore, the reserved cavity is filled with sound-absorbing material or other functional substances by injection filling or vacuum filling process, the injection pressure range is 0.1MPa-1MPa, and the vacuum degree range is -0.05MPa--0.1MPa.

[0019] Furthermore, an antioxidant is added to the composite intermediate layer, and the antioxidant is a hindered phenol antioxidant, and its mass fraction in the composite intermediate layer is 0.5%-5%, preferably 1%-3%. The molecular weight range of the hindered phenol antioxidant is 300-800, the hydroxyl equivalent is 100-400, and the melting point range is 50°C-180°C. The antioxidant can effectively prevent the conductive material, thermal conductive material and other functional components from deteriorating due to oxidation during long-term use, thereby further improving the service life and performance stability of the multi-layer conductive foam in a complex environment, and ensuring that it can continue to play an effective role in electromagnetic shielding, thermal conductivity and heat dissipation, sound absorption and noise reduction or other special functional applications.

[0020] Compared with the prior art, this multi-layer conductive foam has the following beneficial effects:

[0021] 1. The multi-layer conductive foam uses nano silver wire as a conductive material and combines graphene or boron nitride as a thermal conductive material to construct an efficient electromagnetic shielding and thermal conductive network. Nano silver wire can effectively block the penetration of electromagnetic waves due to its excellent conductive properties and provide excellent electromagnetic shielding effect. At the same time, graphene and boron nitride, as high-performance thermal conductive materials, can quickly conduct heat away to avoid local overheating. The combination of these two materials makes the multi-layer conductive foam perform well in electromagnetic shielding and thermal conductivity, and is suitable for electronic devices with high requirements for electromagnetic shielding and heat dissipation.

[0022] 2. The multi-layer conductive foam adds quantum dot-doped polymer materials, bio-based nanocomposites and antioxidants in the composite middle layer. The introduction of these additives significantly enhances the stability and service life of the material. Quantum dot-doped polymer materials can improve the overall performance of the material, such as optical, electrical and thermal properties, and bio-based nanocomposites give the material better biocompatibility and degradability, which meets environmental protection requirements. In addition, the addition of antioxidants can effectively prevent the performance degradation of conductive materials, thermal conductive materials and other functional components due to oxidation during long-term use, thereby further improving the service life and performance stability of the multi-layer conductive foam in complex environments.

[0023] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0025] Figure 1 This is a multi-layer conductive foam process operation diagram. DETAILED DESCRIPTION

[0026] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.

[0027] Comparative Example

[0028] Nano silver wires are selected, with a diameter of 50 nm, a length of 50 μm, and a mass fraction of 10% in the composite middle layer.

[0029] Graphene is used, with 5 layers, a sheet diameter of 50 μm, and a mass fraction of 10% in the composite middle layer.

[0030] The quantum dots are cadmium sulfide quantum dots with a particle size of 10 nm and a mass fraction of 5% in the quantum dot-doped polymer material. The polymer is a polyurethane polymer.

[0031] The chitin nanofiber has a diameter of 50 nm and a length of 50 μm, the silver nanoparticle has a particle size of 20 nm, and the mass fraction of the silver nanoparticle in the bio-based nanocomposite material is 20%.

[0032] Prepare the above-mentioned proportions of conductive material (nanosilver wire), thermal conductive material (graphene) and antioxidant (hindered phenol antioxidant, molecular weight of 500, hydroxyl equivalent of 200, melting point of 100°C, mass fraction of 2%).

[0033] Epoxy resin adhesive is used, and the coating amount of the adhesive on the bonding interface is 50g / m 2 .

[0034] Choose sound-absorbing materials, such as sound-absorbing cotton.

[0035] Embodiment 1

[0036] According to the above comparative example, only the content of the conductive material is changed, and nano silver wires are selected, the diameter of which is 50 nm, the length is 50 μm, and the mass fraction in the composite intermediate layer is 30%.

[0037] Graphene is used, with 5 layers, a sheet diameter of 50 μm, and a mass fraction of 10% in the composite middle layer.

[0038] The quantum dots are cadmium sulfide quantum dots with a particle size of 10 nm and a mass fraction of 5% in the quantum dot-doped polymer material. The polymer is a polyurethane polymer.

[0039] The chitin nanofiber has a diameter of 50 nm and a length of 50 μm, the silver nanoparticle has a particle size of 20 nm, and the mass fraction of the silver nanoparticle in the bio-based nanocomposite material is 20%.

[0040] Prepare the above-mentioned proportions of conductive material (nanosilver wire), thermal conductive material (graphene) and antioxidant (hindered phenol antioxidant, molecular weight of 500, hydroxyl equivalent of 200, melting point of 100°C, mass fraction of 2%).

[0041] Epoxy resin adhesive is used, and the coating amount of the adhesive on the bonding interface is 50g / m 2 .

[0042] Choose sound-absorbing materials, such as sound-absorbing cotton.

[0043] Effect: By increasing the mass fraction of nano silver wire in the composite middle layer to 30%, the electrical and thermal conductivity are significantly optimized, the resistance is further reduced to about 0.1 ohm, the thermal conductivity is increased to 6-9W / (m·K), and the sound absorption and antibacterial properties remain stable. It shows unique advantages in multi-field application scenarios with stringent requirements on electrical and thermal conductivity and sound absorption and antibacterial needs, and provides a better material selection solution for high-end electronic equipment and special functional protective facilities.

[0044] Embodiment 2

[0045] According to the above comparative example 2, only the content of the heat-conducting material is changed, and nano silver wires are selected, with a diameter of 50 nm, a length of 50 μm, and a mass fraction of 10% in the composite intermediate layer.

[0046] Graphene is used, with 5 layers, a sheet diameter of 50 μm, and a mass fraction of 20% in the composite middle layer.

[0047] The quantum dots are cadmium sulfide quantum dots with a particle size of 10 nm and a mass fraction of 5% in the quantum dot-doped polymer material. The polymer is a polyurethane polymer.

[0048] The chitin nanofiber has a diameter of 50 nm and a length of 50 μm, the silver nanoparticle has a particle size of 20 nm, and the mass fraction of the silver nanoparticle in the bio-based nanocomposite material is 20%.

[0049] Prepare the above-mentioned proportions of conductive material (nanosilver wire), thermal conductive material (graphene) and antioxidant (hindered phenol antioxidant, molecular weight of 500, hydroxyl equivalent of 200, melting point of 100°C, mass fraction of 2%).

[0050] Epoxy resin adhesive is used, and the coating amount of the adhesive on the bonding interface is 50g / m 2 .

[0051] Choose sound-absorbing materials, such as sound-absorbing cotton.

[0052] Effect: This embodiment significantly improves the thermal conductivity by increasing the mass fraction of graphene in the composite middle layer to 20% while sacrificing a small amount of electrical conductivity (slightly increased resistance), and the thermal conductivity coefficient reaches 8-11W / (m·K), while the sound absorption and antibacterial properties remain stable. This makes the multi-layer conductive foam have greater advantages in scenarios with high requirements for heat dissipation, relatively loose requirements for electrical conductivity, and requirements for sound absorption and antibacterial properties, such as protection and heat dissipation of high-power electronic equipment, and industrial equipment housings with certain requirements for hygiene and acoustic environments, providing a performance-optimized material solution for related fields.

[0053] Embodiment 3

[0054] According to the above comparative example 3, only the content of the quantum dot-doped polymer material is changed, and nano silver wires are selected, with a diameter of 50 nm, a length of 50 μm, and a mass fraction of 10% in the composite intermediate layer.

[0055] Graphene is used, with 5 layers, a sheet diameter of 50 μm, and a mass fraction of 10% in the composite middle layer.

[0056] The quantum dots are cadmium sulfide quantum dots with a particle size of 10 nm and a mass fraction of 15% in the quantum dot-doped polymer material. The polymer is a polyurethane polymer.

[0057] The chitin nanofiber has a diameter of 50 nm and a length of 50 μm, the silver nanoparticle has a particle size of 20 nm, and the mass fraction of the silver nanoparticle in the bio-based nanocomposite material is 20%.

[0058] Prepare the above-mentioned proportions of conductive material (nanosilver wire), thermal conductive material (graphene) and antioxidant (hindered phenol antioxidant, molecular weight of 500, hydroxyl equivalent of 200, melting point of 100°C, mass fraction of 2%).

[0059] Epoxy resin adhesive is used, and the coating amount of the adhesive on the bonding interface is 50g / m 2 .

[0060] Choose sound-absorbing materials, such as sound-absorbing cotton.

[0061] Effect: In this embodiment, by increasing the mass fraction of quantum dots in the quantum dot-doped polymer material to 15%, the sound absorption performance is optimized to a certain extent while the electrical and thermal conductivity properties remain basically unchanged. The sound absorption coefficient in the audio range of 100Hz-5000Hz is improved, which can more effectively reduce noise, while the antibacterial performance remains stable. This makes the multi-layer conductive foam more advantageous in scenarios that have high requirements for the acoustic environment and require electrical conductivity, thermal conductivity and antibacterial properties, such as acoustic shielding of electronic equipment and production workshops with requirements for hygiene and noise control, providing a more suitable material selection for related fields.

[0062] Embodiment 4

[0063] According to the above comparative example 4, only the content of the bio-based nanocomposite material is changed, and nano silver wires are selected, the diameter of which is 50 nm, the length of which is 50 μm, and the mass fraction of which in the composite intermediate layer is 10%.

[0064] Graphene is used, with 5 layers, a sheet diameter of 50 μm, and a mass fraction of 10% in the composite middle layer.

[0065] The quantum dots are cadmium sulfide quantum dots with a particle size of 10 nm and a mass fraction of 5% in the quantum dot-doped polymer material. The polymer is a polyurethane polymer.

[0066] The chitin nanofiber has a diameter of 50 nm and a length of 50 μm, the silver nanoparticle has a particle size of 20 nm, and the mass fraction of the silver nanoparticle in the bio-based nanocomposite material is 40%.

[0067] Prepare the above-mentioned proportions of conductive material (nanosilver wire), thermal conductive material (graphene) and antioxidant (hindered phenol antioxidant, molecular weight of 500, hydroxyl equivalent of 200, melting point of 100°C, mass fraction of 2%).

[0068] Epoxy resin adhesive is used, and the coating amount of the adhesive on the bonding interface is 50g / m 2 .

[0069] Choose sound-absorbing materials, such as sound-absorbing cotton.

[0070] Effect: This embodiment greatly improves the antibacterial performance by increasing the mass fraction of silver nanoparticles in the bio-based nanocomposite material to 40%, while keeping the electrical conductivity, thermal conductivity and sound absorption properties basically stable. The antibacterial rate against Escherichia coli and Staphylococcus aureus is increased to more than 95%, and the concentration of viable bacteria is significantly reduced. This makes the multi-layer conductive foam more competitive in scenarios with extremely strict hygiene requirements and the need for electrical conductivity, thermal conductivity and sound absorption properties, such as high-level medical equipment protection, noise reduction and protection in food processing workshops with high hygiene standards, providing a material solution with stronger antibacterial properties for related fields.

[0071] Embodiment 5

[0072] According to the above comparative example 5, only the content of the composite intermediate layer material is changed, and nano silver wires are selected, with a diameter of 50 nm, a length of 50 μm, and a mass fraction of 10% in the composite intermediate layer.

[0073] Graphene is used, with 5 layers, a sheet diameter of 50 μm, and a mass fraction of 10% in the composite middle layer.

[0074] The quantum dots are cadmium sulfide quantum dots with a particle size of 10 nm and a mass fraction of 5% in the quantum dot-doped polymer material. The polymer is a polyurethane polymer.

[0075] The chitin nanofiber has a diameter of 50 nm and a length of 50 μm, the silver nanoparticle has a particle size of 20 nm, and the mass fraction of the silver nanoparticle in the bio-based nanocomposite material is 20%.

[0076] Conductive material (nanosilver wire), thermal conductive material (graphene) and antioxidant (hindered phenol antioxidant, molecular weight of 500, hydroxyl equivalent of 200, melting point of 100°C, mass fraction of 5%) in the above proportions are prepared, and the antioxidant content is increased to further improve the stability of the material.

[0077] Epoxy resin adhesive is used, and the coating amount of the adhesive on the bonding interface is 50g / m 2 .

[0078] Choose sound-absorbing materials, such as sound-absorbing cotton.

[0079] Effect: This embodiment increases the mass fraction of hindered phenol antioxidant in the composite middle layer to 5%. While maintaining stable sound absorption performance, the electrical conductivity, thermal conductivity and antibacterial properties are optimized to a certain extent. The resistance is slightly reduced to about 0.51 ohms, the thermal conductivity is increased to 6-9W / (m·K), and the antibacterial rate is increased to more than 92%. This makes the multi-layer conductive foam more valuable in scenarios that have higher requirements for electrical conductivity, thermal conductivity and antibacterial properties and require sound absorption functions, such as comprehensive protection of high-performance electronic equipment and industrial production environments with dual requirements for hygiene and acoustic environments. It provides a material selection solution with better performance for related fields.

[0080] The specific contents are shown in the following table:

[0081]

[0082]

[0083] As described in the table above, the above five embodiments respectively change the contents of conductive materials, thermal conductive materials, quantum dot-doped polymer materials, bio-based nanocomposites, and composite intermediate layer materials in the multi-layer conductive foam, and the other parameters remain unchanged. When the content of the conductive material is changed, the resistance changes significantly, and the effects on thermal conductivity, sound absorption, and antibacterial properties are different. When the content of the thermal conductive material is adjusted, the thermal conductivity is improved while the conductivity, sound absorption, and antibacterial properties are affected to varying degrees. The change in the content of the quantum dot-doped polymer material mainly optimizes the sound absorption effect, and the conductivity, thermal conductivity, and antibacterial properties are relatively stable. The increase in the content of the bio-based nanocomposite material greatly enhances the antibacterial ability, and other properties are basically unchanged. The increase in the content of the antioxidant in the composite intermediate layer material optimizes the conductivity, thermal conductivity, and antibacterial properties to a certain extent, while the sound absorption performance remains constant. These embodiments fully demonstrate the differentiated effects of changes in the content of different materials on the comprehensive performance of the multi-layer conductive foam and the expansion of potential application directions.

[0084] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A multi-layer conductive foam, characterized in that: It is composed of the following components: conductive material, thermal conductive material, quantum dot-doped polymer material and bio-based nanocomposite material, and a composite middle layer is compositely assembled with other foam layers through a lamination or bonding process and a cavity is reserved; The conductive material is nano silver wire; The thermal conductive material is graphene or boron nitride; The quantum dots doped with the polymer material are cadmium sulfide quantum dots, and the polymer is a polyurethane polymer; The bio-based nanocomposite material is a composite of chitin nanofibers and silver nanoparticles; The composite middle layer is compositely assembled with other foam layers through lamination or bonding process; The reserved cavity is filled with sound absorbing material or other functional substances by injection filling or vacuum filling process.

2. The multi-layer conductive foam according to claim 1, characterized in that: The conductive material is nano silver wire, the diameter of which is in the range of 10nm-100nm, the length of which is in the range of 1μm-100μm, and the mass fraction of which in the composite middle layer is 5%-20%.

3. The multi-layer conductive foam according to claim 1, characterized in that: The thermal conductive material is graphene or boron nitride, wherein the number of graphene layers is 1-10, the sheet diameter ranges from 1 μm to 100 μm, and the mass fraction in the composite middle layer is 3%-15%, and the boron nitride is hexagonal boron nitride, the particle diameter ranges from 0.5 μm to 50 μm, and the mass fraction in the composite middle layer is 3%-15%.

4. The multi-layer conductive foam according to claim 1, characterized in that: The quantum dots in the quantum dot-doped polymer material are cadmium sulfide quantum dots, the particle size range of which is 2nm-20nm, the mass fraction of which in the quantum dot-doped polymer material is 1%-10%, and the polymer is a polyurethane polymer.

5. The multi-layer conductive foam according to claim 1, characterized in that: The bio-based nanocomposite material is a composite of chitin nanofibers and silver nanoparticles. The chitin nanofibers have a diameter range of 10nm-100nm and a length range of 1μm-100μm. The silver nanoparticles have a particle size range of 5nm-50nm. The mass fraction of the silver nanoparticles in the bio-based nanocomposite material is 5%-30%.

6. The multi-layer conductive foam according to claim 1, characterized in that: The composite middle layer is compositely assembled with other foam layers by lamination or bonding process, the lamination pressure range is 0.5MPa-5MPa, the adhesive is epoxy resin adhesive, and the coating amount of the adhesive on the bonding interface is 10g / m 2 -100g / m 2 .

7. The multi-layer conductive foam according to claim 1, characterized in that: The reserved cavity is filled with sound-absorbing material or other functional substances by injection filling or vacuum filling process, the injection pressure range is 0.1MPa-1MPa, and the vacuum range is -0.05MPa--0.1MPa.

8. The multi-layer conductive foam according to claim 1, characterized in that: The composite intermediate layer also contains an antioxidant, which is a hindered phenol antioxidant. Its mass fraction in the composite intermediate layer is 0.5%-5%, preferably 1%-3%. The hindered phenol antioxidant has a molecular weight range of 300-800, a hydroxyl equivalent of 100-400, and a melting point range of 50°C-180°C.